2012
DOI: 10.1007/s10773-012-1164-0
|View full text |Cite
|
Sign up to set email alerts
|

On Conformally Flat Almost Pseudo-Ricci Symmetric Spacetimes

Abstract: We consider a conformally flat almost pseudo-Ricci symmetric spacetime. At first we show that a conformally flat almost pseudo-Ricci symmetric spacetime can be taken as a model of the perfect fluid spacetime in general relativity and cosmology. Next we show that if in a conformally flat almost pseudo-Ricci symmetric spacetime the matter distribution is perfect fluid whose velocity vector is the vector field corresponding to 1-form B of the spacetime, the energy density and the isotropic pressure are not consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
(18 reference statements)
3
16
0
Order By: Relevance
“…De and Ghosh [11] showed that if R ij = Ag ij + Bu i u j with u i closed and C ijkl = 0, then u is a concircular vector. The results were extended by Mantica et al to pseudo Z-symmetric spaces [24] and to weakly Z-symmetric spaces [25].…”
Section: Introductionmentioning
confidence: 99%
“…De and Ghosh [11] showed that if R ij = Ag ij + Bu i u j with u i closed and C ijkl = 0, then u is a concircular vector. The results were extended by Mantica et al to pseudo Z-symmetric spaces [24] and to weakly Z-symmetric spaces [25].…”
Section: Introductionmentioning
confidence: 99%
“…, x 4 are the standard coordinates of R 4 . We note that such type of metric was first appeared in [89] and latter used by many authors (see [15,16,100]) to prove the existence of various curvature restricted geometric structures. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 93%
“…If in the above equation B = A, then the (AP S) n reduces to a(P S) n . In subsequent papers ( [11], [12]) De and Gazi studied almost pseudo conformally symmetric manifolds and conformally flat almost pseudo Ricci symmetric manifolds. It may be mentioned that (P S) n is a particular case of an (AP S) n , but(W S) n is not a particular case of an (AP S) n .…”
Section: +E(w )R(y Z)x + G(r(y Z)w X)pmentioning
confidence: 99%